STRATEGI REDAKSI BERITA RISET DAN INOVASI PADA WEBSITE PPID BRIN - Fitriani, Reni; Dermawan, Riyan (Mediakom : Jurnal Ilmu Komunikasi, 2025)
This study aims to explore and explain the editorial policies of the PPID BRIN as an educational medium related to research and innovation. The theory used is the gatekeeping theory or shoemaker theory. This theory explains that the role of editors or gatekeepers is very important in disseminating information. The research method used is a qualitative descriptive method. Data collection techniques used include observation, in-depth interviews, and documentation. The paradigm used in this study is the constructivism paradigm. The researcher used source triangulation as a way of collecting data. The subjects in this study were employees at PPID BRIN, especially the editorial team that had been determined by the researcher based on established criteria. The results of the study indicate that factors in the gatekeeping theory influence the process of information dissemination. PPID BRIN always implements an unwritten editorial policy so that information conveyed to the public can be conveyed properly and correctly. The news delivered on the PPID BRIN website is a reflection of PPID BRIN's organizational culture which prioritizes openness, transparency, and accountability in disseminating public information in the realm of research and innovation. Furthermore, as an online public relations tool, the most important requirement is an awareness of the importance of public services for adequate information and the accuracy of which can be accounted for.